Part 6. (1st June 2015) - Davis, Christine; Lyall, Scott; P., Paul; Balfour, Ian; Stengers, Isabelle
Entries: Contemporaries, Saturation, Noir, Settlements, Seeds, Trees, Audio Cryptograms, Includes text by Christine Davis, Scott Lyall, Paul P., Ian Balfour, Isabelle Stengers. Artworks by Jack Kath, Fiona Annis, Silke Otto-Knapp, Stephen Andrews, Mario Doucette, Nadia Myre, Charles Gaines, Blake Rayne, Charles E.Burchfield, Nancy WeeklyPoem by Eleni Sikelianos